Optimization of Extraction Method of Hyoscine from Hyoscyamus niger L. - R Ghafarzadegan; P Khadiv-parsi; F Khalighi-Sigaroodi; M Pirali Hamedani; Z Kadkhoda; Sh Rezazadeh (Institue of Medicinal Plants, ACECR, 2010)
Background: Hyoscyamus niger L. from Solanaceae is an important pharmacological plant which contains tropane alkaloids. tropane alkaloids constitute one distinct group of secondary metabolites of the Solanaceae. Hyoscyamus species are rich source of tropane alkaloids, mainly hyoscyamine and hyoscine (scopolamine), which are widely used for their mydriatic,antispasmodic, anticholinergic, analgesic and sedative properties. Therefore determine of optimized method is necessary for extraction of hyoscine from Hyoscyamus niger L. Objective: The purpose of this research is determine of optimized conditions for extraction of hyoscine from Hyoscyamus niger L. Methods: Three factors, temperature, extraction time and mesh size of plant were studied using three level box-behnken design. the hyoscine content were measured by Gas chromatograph, Younglin Acm 6000 model. Results: The results showed that the best conditions for extraction of hyoscine from Hyoscyamus niger L. is Ultrasonic extraction in 43 C, 130 min and 45 mesh size. Conclusion: It can be concluded that in order to efficient extraction of hyoscine from Hyoscyamus niger L., special conditions should be considered.